The Impact of Teachers Interpersonal Characteristics on Acquisition of Reading Skills among Grade Three Pupils in Public Primary Schools in Bungoma County, Kenya (Proceedings of the International Conference on Future of Education, 2021)
The acquisition of requisite reading skills plays a crucial role in scaffolding learning andmore so when children start their education. These reading skills form an important pivot aroundwhich most learning revolves. Nevertheless, studies globally indicate that majority of school-agepupils are not being taught the relevant reading skills at an appropriate age and grade hence most ofthem attain the age of eleven years before acquiring these skills. The integral role played by theteacher in enabling learners to acquire reading skills cannot be over-emphasized. They are, in fact, animportant axis around which all educational processes revolve including the success in theacquisition of the children‟s literacy skills. The purpose of this study was to find out the impact ofteacher interpersonal characteristics on the acquisition of reading skills among grade three pupils inpublic primary schools in Bungoma County, Kenya. Vygotsky‟s (1978) theory was fundamental tothis study. A descriptive survey research was adopted in the study focusing on grade three pupils,their class teacher and the headteachers in Bumula Sub-County. Simple random sampling andpurposive sampling techniques were used to select the study sample of 32%. Data was collectedusing questionnaires, interview schedules and reading tests for grade three pupils to determine theirlevel of reading skills. The researcher designed a pupil test to determine the levels of reading acrossthe Grade III Learners. The study found out that teachers‟ interpersonal characteristics had an impacton the acquisition of reading skills among the grade III learners. The study further established thatGrade III pupils in Bungoma County have overall poor reading skills as manifested by their dismalsound recognition, comprehension, word recognition, and reading fluency. Furthermore, the studyestablished that Grade III teachers are neither aware nor apply their interpersonal skills, but rely ontheir skills to help Grade III learners acquire reading skills. The study recommended that BungomaCounty‟s Ministry of Education should use these findings for policy implementation as a way orimproving teacher interpersonal relationships, through modification of the curriculum of teachertraining colleges
Keywords: Acquisition; Impact; Interpersonal characteristics; Reading skill